Grey relational analysis and optimization of guide vane for reactor coolant pump in the coasting transient process. (November 2019) - Wang, Xiuli; An, Ce; Fu, Qiang; Zhu, Rongsheng; Lu, Yonggang; Cai, Zheng; Jiang, Xiafei
Abstract: The coasting behavior of the reactor coolant pump is one of the important indicators for the safe operation of the nuclear power system. In order to ensure the optimal coasting behavior of the reactor coolant pump under the power cutoff accident condition, this manuscript takes the guide vanes of AP1000 reactor coolant pump as the subject of this study and the main factors parameters of the vanes as optimization variables, and aims to reduce the flow loss and uniform the velocity distribution in the flow channel. And based on the orthogonal experimental design and grey relational analysis method, this manuscript analyzes, optimizes and verifies the correlation degree of the main factors parameters of the guide vanes of the reactor coolant pump. The results show that three factors of the vane wrap angle φ, the guide impeller clearance Rt and the outlet blade angle α4, have a great influence on the efficiency and head. The correlation degree of each factor is ranked as α4, φ, Rt, α3, δ, b 4 . The optimized guide vane evidently improves the efficiency and head of the pump in small flow conditions. On the basis of the unchanged or improved performance parameters corresponding to the design conditions, the high efficient zone shift to small flow, the coasting time extends, and the coasting behavior is optimized.